Economic analysis of pricing policies of meat products in Iraq - Hussein, Sarmad Ali (2017)
Price policy is a tool used to motivate producers to increase production. It aims to balance the interests of producers and consumers, as well as the government. Demand for meat in Iraq has increased significantly over the years. The livestock sector is suffering from higher prices and an increase in costs. There are two (2) approaches to support which can be output price or input price policies. These policies require considerable funds from the government treasury. This study examines the effects of state intervention in the pricing of meat products (beef and fish) in Iraq for the period 1985-2013. It aims to measure protection coefficients to determine whether support is benefit of producers or consumers. Also to determine multiple effects of the single market model for government policy of output price support and input price support.